Influencing factors Fraud Prevention : Internal Control , Management Risk and Whistleblowing System - Nanin Pattingalloang; Cris Kuntadi (Sean Institute, 2024)
Fraud prevention is remove chance or opportunity commit fraud with build and implement management risks ( esp management risk of fraud), Internal Control and honest Corporate Governance . Fraud Prevention​ Alone is activity combat fraud by cheap cost .​ Prevention fraud Can analogous with disease , that is more Good prevented than treated . This article discuss about influencing factors​ Fraud Prevention , ie Internal Control , Management Risk and Whistleblowing System . Writing purpose article This To use build hypothesis influence between variable For used in research furthermore . Results of this literature review article are : 1) Internal Control influential to Fraud Prevention ; 2) Management Risk influential to Fraud Prevention ; and 3) Whistleblowing System influential to Fraud Prevention.